The Indian Ocean and Swahili Coast coins, international networks and local developments - John Perkins (Afriques)
The distinctive coinage of the Swahili Coast (c. 800–1500) has for a long time been seen as a barbarized coinage on the edge of the Islamic world, a product of colonial settlements of Arabs and Persians. With new evidence becoming available, the towns have taken their place as flourishing African trading ports, homogenously developed from local villages. One of the most durable remains of archaeological material culture in these towns, the coins, has not received the same attention, despite their being one of the keys to further understanding the Swahili stone towns. By deconstructing the previous hunt for precedents, it is argued that the coins are a stand-out marker of the Swahili stone town culture and not simply poor copies of other Islamic Indian Ocean coinages. However, their role both on the Swahili Coast and the Indian Ocean world is still poorly understood; and in the search for a clearer idea of their purpose, this paper not only looks at them from a local perspective, but also looks at the wider implications for coin use in the Indian Ocean trade.